Antioxidant Activity of Fungus Comb Extracts Isolated from Indo-Malayan Termite Macrotermes gilvus Hagen (Isoptera: Termitidae) - Yanti Rachmayanti; Dikhi Firmansyah; Reza Ro'isatul Umma; Decsa Medika Hertanto; I Ketut Sudiana; Djoko Santoso; Dodi Nandika; Lina Karlinasari; Arinana Arinana; Irmanida Batubara; Lucia Dhiantika Witasari (Universitas Gadjah Mada, 2022)
Indonesian termites are one of the wealthiest biological resources considering their very high species diversity (300 species) and extensive geographical distribution in the Indonesian mainland. However, its potential as a source of bioactive compounds has not been fully explored. One of the endemic termite sub-families of Indonesian, Macrotermitinae (Isoptera: Termitidae), has a food source in the form of fungal nodules that grow and spread in a particular structure in the termite nest that is shaped like a mammalian brain called a fungus comb, which likely serves as a source of bioactive compounds. This study aims to analyze the potential of fungus comb from an Indonesian Macrotermitinae sub-family species as a source of antioxidants. Antioxidant activity was tested on four different extracts of fungus comb (EFC), namely hexane extract, ethyl acetate extract, methanol extract and water extract, using DPPH• (1,1-diphenyl-2-picrylhydrazyl) and ABTS•+ (2,2′-azino-di-[3-ethylbenzthiazolinesulphonate]) radicals. The results showed that the highest antioxidant activity was found in methanol extract, followed by ethyl acetate extract with IC50 values of 0.6 mg/mL and 0.75 mg/mL, respectively. TEAC (Trolox equivalent antioxidant capacity) analysis confirmed the high antioxidant activity of methanol extract.